1999
DOI: 10.1679/aohc.62.129
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ATP and Its Analogues on (Ca2+)i Dynamics in the Rabbit Corneal Epithelium.

Abstract: Adenosine-5'-triphosphate (ATP) plays a pivotal role in various tissues as an extracellular transmitter. ATP released from nerve endings and/or damaged cells may elicit reactions in adjacent cells. To identify such reactions, we investigated the dynamics of the intracellular calcium ion concentrations ([Ca2+]i) in the rabbit corneal epithelium during ATP-stimulation. Intact epithelial sheets isolated from corneal tissue were loaded with Fura-2, and [Ca2+]i dynamics in each cell layer were analyzed using a digi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 30 publications
3
13
0
Order By: Relevance
“…2), since ligand binding to a receptor expressed on the cellsurface is required for a response to occur. Furthermore, the Ca 2þ imaging results for the corneal epithelial cell line corresponded with those for primary epithelial cells isolated from rabbit corneas [Kimura et al, 1999] (Fig. 2B,C).…”
Section: Discussionsupporting
confidence: 61%
“…2), since ligand binding to a receptor expressed on the cellsurface is required for a response to occur. Furthermore, the Ca 2þ imaging results for the corneal epithelial cell line corresponded with those for primary epithelial cells isolated from rabbit corneas [Kimura et al, 1999] (Fig. 2B,C).…”
Section: Discussionsupporting
confidence: 61%
“…Furthermore, our data showed that ADP induces low-level HB-EGF shedding and has no effect on wound closure, a result consistent with a recent report (Mediero et al, 2006), suggesting that ATP, but not ADP, serves as one of the initial signals to trigger wound response in HCE cells. Previous studies, using various inhibitors, showed that P2Y but not P2X receptors are responsible for ATP-induced Ca 2+ dynamics in human and rabbit corneal epithelium (Kimura et al, 1999;Klepeis et al, 2004). To assess the involvement of extracellular ATP in epithelial wound healing, we used two purinoceptor inhibitors suramin and RB2 to determine the effects of P2Y blockade on HCE cell wound healing.…”
Section: Fig 7 Atp-␥-s-induced Hb-egf Shedding and Egfr Activation mentioning
confidence: 99%
“…P2Y2 receptors have been identified in a wide variety of ocular cell types, particularly, in retina [26], retinal pigment epithelium [27][28][29], cornea [30,31], conjunctiva [32], lens [33], and ciliary epithelia [9,34]. P2Y2 receptor signaling and its function are apparent in the eye [35], and regulates multiple cellular functions in ocular physiology by calcium mobilization [9] including ion transport and fluid absorption [27,29], and mucin discharge [36].…”
Section: Discussionmentioning
confidence: 99%